Planning For Bonebula Beach Tourism Objects In Towale Village, Central Banawa District Donggala Regency - Budianta, Aziz; Andriansyah (Tadulako Social Science and Humaniora Journal, 2022)
This research aims to find out the physical feasibility of bonebula beach which is then continued by measuring the matrix of land suitability that has been owned by Bonebula Beach to become viable as a beach tourism object, then developed using SWOT analysis method to make Bonebula beach one of the favorite tourist attractions in Donggala Regency, especially beach tourism objects. The type of research conducted is quantitative descriptive with the geographical approach used that is the ecological approach. This research uses observation techniques and measurements directly in the field as well as data collection through library study. The results showed that bonebula beach is broadly in the appropriate category (S2) to be developed into a coastal tourist attraction with indicators of land suitability being at a value of 380 with the provision of land conformity matrix value S1= >400, S2= 200 -400, S3= 100-200, and NT= <100. While the feasibility level of Bonebula Beach tourism was developed by SWOT analysis method, the matrix used in this study using ifas matrix and EFAS obtained SWOT diagram with SO strategy that has strength and opportunity. Bonebula Beach Tourism Object has a great opportunity as a favorite tourist destination in Donggala Regency. the matrix used in this study using ifas matrix and EFAS obtained SWOT diagram with SO strategy that has strength and opportunity. Bonebula Beach Tourism Object has a great opportunity as a favorite tourist destination in Donggala Regency. the matrix used in this study using ifas matrix and EFAS obtained SWOT diagram with SO strategy that has strength and opportunity. Bonebula Beach Tourism Object has a great opportunity as a favorite tourist destination in Donggala Regency